Analogues of Disulfides from Allium stipitatum Demonstrate Potent Anti-tubercular Activities through Drug Efflux Pump and Biofilm Inhibition - Cynthia A. Danquah (Nature Portfolio, 2018)
Abstract Disulfides from Allium stipitatum, commonly known as Persian shallot, were previously reported to possess antibacterial properties. Analogues of these compounds, produced by S-methylthiolation of appropriate thiols using S-methyl methanethiosulfonate, exhibited antimicrobial activity, with one compound inhibiting the growth of Mycobacterium tuberculosis at 17 µM (4 mg L−1) and other compounds inhibiting Escherichia coli and multi-drug-resistant (MDR) Staphylococcus aureus at concentrations ranging between 32–138 µM (8–32 mg L−1). These compounds also displayed moderate inhibitory effects on Klebsiella and Proteus species. Whole-cell phenotypic bioassays such as the spot-culture growth inhibition assay (SPOTi), drug efflux inhibition, biofilm inhibition and cytotoxicity assays were used to evaluate these compounds. Of particular note was their ability to inhibit mycobacterial drug efflux and biofilm formation, while maintaining a high selectivity towards M. tuberculosis H37Rv. These results suggest that methyl disulfides are novel scaffolds which could lead to the development of new drugs against tuberculosis (TB).